Konstruksi Hukum dalam Standarisasi Tata Kelola Perencanaan Pembangunan Daerah untuk Mendukung Efektivitas Pembangunan Nasional - Sipahutar, Ervina Sari (Universitas Medan Area, 2025)
Regional development planning is a crucial component of the national development system. However, decentralization and variations in institutional capacity across regions pose serious challenges to the uniformity and effectiveness of planning governance. This study aims to analyze the role of legal construction in promoting the standardization of regional development planning governance to support the effectiveness of national development. Using a normative juridical approach, this research applies a literature review method focusing on laws and regulations, policy documents, and relevant academic literature. The findings indicate that a strong and adaptive legal framework is essential to establish a well-coordinated, data-driven planning system that is responsive to long-term development needs. The main obstacles identified include overlapping regulations, disparities in institutional capacity, and the suboptimal application of accountability and public participation principles. The study recommends regulatory harmonization between central and regional governments, strengthening the capacity of planning institutions, and developing an integrated information system with clear legal provisions. In conclusion, an effective legal construction serves as a fundamental foundation for creating a standardized governance structure for regional development planning, capable of accelerating and sustaining national development.